The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/obr.13336
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐glucose co‐transporter 2 inhibitors on weight change and cardiometabolic profiles in individuals with overweight or obesity and without diabetes: A meta‐analysis

Abstract: Summary Several meta‐analyses have been conducted to evaluate the weight loss effect of sodium–glucose cotransporter 2 (SGLT‐2) inhibitors in patients with type 2 diabetes, whereas pooled analysis focusing on individuals without diabetes is lacking. The objective of this systematic review and meta‐analysis is to evaluate the effect of SGLT‐2 inhibitor monotherapy on weight change and cardiometabolic profiles. Multiple databases were searched for randomized controlled trials reporting weight change effect of SG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The primary outcome was absolute weight loss after intervention. With reference to a previous meta-analysis of RCTs that examined cardiometabolic outcomes [16], cardiometabolic parameters, including BMI, waist circumference (WC), body fat mass (BFM), total cholesterol (TC), high-density lipoproteincholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglycerides (TG), fasting plasma glucose (FPG)/fasting glucose (GLU), homeostatic model assessment of insulin resistance (HOMA-IR), systolic blood pressure (SBP), and diastolic blood pressure (DBP), were selected as secondary outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome was absolute weight loss after intervention. With reference to a previous meta-analysis of RCTs that examined cardiometabolic outcomes [16], cardiometabolic parameters, including BMI, waist circumference (WC), body fat mass (BFM), total cholesterol (TC), high-density lipoproteincholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglycerides (TG), fasting plasma glucose (FPG)/fasting glucose (GLU), homeostatic model assessment of insulin resistance (HOMA-IR), systolic blood pressure (SBP), and diastolic blood pressure (DBP), were selected as secondary outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrients 2024, 16, 357 2 of 15 Various forms of fasting have been developed, including intermittent fasting (IF), calorie restriction, long-term fasting, very low-calorie diet, and fasting-mimicking diet [6]. In recent years, IF has been an emerging dietary intervention for weight management.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a meta-analysis involving seven studies with 2297 participants indicated that SGLT-2 inhibitor plus MET was superior to MET for weight control in people with type 2 diabetes for no more than 52 weeks ( 43 ). Another meta-analysis of eight studies with 750 individuals found that SGLT-2 inhibitor monotherapy for 12 weeks or more could lead to modest weight loss in non-diabetic overweight and obese individuals ( 44 ). This discordance might be due to the relatively short duration of the intervention or the different diseases and populations.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, SGLT-2 inhibitors may also reduce the risk of retinopathy in T2DM patients 7 . In addition, SGLT-2 inhibitors have been recommended as an evidence-based therapeutic option for the management of overweight/obese patients with 8 and without T2DM 9 . These findings suggested that besides the glucose-lowering efficacy, other mechanisms may also be involved in the beneficial efficacies of SGLT-2 inhibitors on cardiorenal outcomes in T2DM patients 10 11 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Original Article: Endocrine Care Influence of Sodium-Glucose Cotransporter-2 Inhibitors on Plasma Adiponectin in Patients with Type 2 Diabetes: A Meta-Analysis of Randomized Controlled Trials evidence-based therapeutic option for the management of overweight/obese patients with [8] and without T2DM [9]. These findings suggested that besides the glucose-lowering efficacy, other mechanisms may also be involved in the beneficial efficacies of SGLT-2 inhibitors on cardiorenal outcomes in T2DM patients [10][11][12].…”
Section: Introductionmentioning
confidence: 99%